(untitled) (Docentes 2.0 Journal, 2020)
This essay is a bibliographic description of virtualization in university organizations and its implementation as a new model of educational management, where the definition of virtualization, virtualization modalities, virtual education model, educational methodology for virtual learning environments will be addressed, organization of virtual education and virtual learning environments. This essay is supported by the dissertations by Sangra (2001), Silva and Romero (2013), and Alba and Orrego (2013) and the book by Silvio (2000).